2018
DOI: 10.21815/jde.018.031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lecture Attendance and Prerequisite Academic Outcomes on Dental Students’ Oral Pathology Performance

Abstract: Decreased lecture attendance in undergraduate and health science professions education has been noted throughout the world. The limited study of the effect of lecture attendance on dental students' performance has yielded mixed results, with some studies finding a positive effect and others reporting no association. The aim of this study was to evaluate the effect of lecture attendance on dental students' final grades in an oral pathology course at one U.S. dental school. Due to a curriculum change, second- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…There may also be value in exploration of bridge programs to supplement undergraduate education for educationally disadvantaged students as well as those with non‐science undergraduate majors or who took science courses at a low credits per term rate. As a recent study linked performance in capstone basic science coursework to early dental school performance as well as DAT Total Science scores, 9 analysis of student performance with respect to the predictor variables used here across the entirety of the first and second years is also warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There may also be value in exploration of bridge programs to supplement undergraduate education for educationally disadvantaged students as well as those with non‐science undergraduate majors or who took science courses at a low credits per term rate. As a recent study linked performance in capstone basic science coursework to early dental school performance as well as DAT Total Science scores, 9 analysis of student performance with respect to the predictor variables used here across the entirety of the first and second years is also warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The DAT PAT has also been linked to success in preclinical operative coursework, 7 and an analysis of performance on a clinical competency exam connected DAT PAT to clinical performance 8 . DAT Total Science (DAT TS) scores have also been found to be associated with success in oral pathology coursework 9 . A study comparing the relationship of admissions criteria and outcomes for average and underachieving dental students found undergraduate GPA to be significantly correlated to first‐year dental GPA for underperforming students 10 .…”
mentioning
confidence: 99%
“…Therefore, additional research should evaluate the relationship of prerequisite admissions criteria to learner performance in the classroom and clinic as well as long‐term outcomes such as licensure or disciplinary action. Research previously conducted has consistently demonstrated minimal relationships between undergraduate grade point average and scores on the National Board Dental Examination Part I, 9 scores on the Comprehensive Basic Sciences Examination, 10 oral pathology class performance, 11 clinical performance, 12 and first‐year course performance 1 …”
Section: Discussionmentioning
confidence: 98%
“…Attendance of lecture was encouraged for dental students to achieve grades. 5 This study aimed to compare the cognitive understanding of MICAP notation (new topic) in relation to Universal tooth notation which is very old notation. The study was approved by the institutional ethics committee of Islamic International Dental College, Islamabad.…”
Section: Micapmentioning
confidence: 99%
“…This system identifies permanent teeth by a series of numbers (1 to 32) for teeth present in permanent dentition. The numbers (1)(2)(3)(4)(5)(6)(7)(8) represent teeth in the upper right quadrant where 3 means upper right 1 st molar. The teeth of upper left quadrant are given numbers (9)(10)(11)(12)(13)(14)(15)(16) where 9 shows upper left central incisor.…”
Section: Introductionmentioning
confidence: 99%